Using Temporal and Spatial Scales to Unravel the Effects of Climatic Factors on Vegetation Variations in China - Jing, Yaodong; Zhu, Hongfen; Bi, Rutian; Hou, Meiting (Frontiers in Ecology and Evolution, 2021)
Geographic time series of vegetation dynamics and climatic factors generally contain spatial or temporal components with different frequency which may significantly affect the overall variance structure in the original data. Based on the half-monthly normalized difference vegetation index (NDVI), half-monthly averaged daily mean temperature (DMT), half-monthly averaged daily range of temperature (DRT), and half-monthly accumulated precipitation (AP), the objective of the study was to explore the multiple temporal-scale effect and multiple spatial-scale effect on the relationships between vegetation growth and climatic factors. The complete ensemble empirical model decomposition (CEEMD) was implemented to decomposed the temporal series of NDVI and climatic factors, and their multiple temporal-scale relationships was examined based on the half-month scale. The two-dimensional empirical mode decomposition (2D-EMD) was implemented to decomposed the spatially distributions of temporal-averaged NDVI and climatic factors, and their multiple spatial-scale relationships was tested based on the sampling scale. The dominant temporal scales of NDVI were around 3-year, 15-year, and > 15-year, while the dominant spatial scales of NDVI were around 2×104 and >10×104 km2. The multiple temporal-scale effect of climatic factors on NDVI was the strongest under mixed forest, and was the lest under broadleaf forest. The positive effect of DMT on NDVI, the negative effect of DRT on NDVI at 200-600 mm precipitation region, and the positive effect of AP on NDVI at 200-1000 mm precipitation region were captured at 15-year temporal scale. The multiple temporal-scale effect of climatic factors on NDVI was greater at the 200-600 precipitation region and Yunnan province, and the area with multiple temporal scale was about 98.08%. The relationships between NDVI and climatic factors at half-month scale and multiple temporal scale differed under different regions of elevation, latitude, longitude, land types, climatic regions, and precipitation. The multiple spatial-scale effect at different spatial scale differed, and the area with multiple spatial scale was about 64.38%. This indicated that multiple temporal scale and multiple spatial scale analysis might unravel an actual understanding of the mechanisms of climatic factors’ effect on vegetation growth, and provide foundation for future vegetation restoration fragile ecosystems.